Konstruksi Hukum dan Dampak Peraturan Menteri PANRB No. 1 Tahun 2023: Efektivitas Administrasi Publik melalui Reformasi Jabatan Fungsional - Chitra Imelda (Kampus Akademik Publiser, 2024)
This study aims to examine the Legal Construction and Impact of Minister of PANRB Regulation No. 1 of 2023 on the effectiveness of public administration through functional position reform in Indonesia. The background of this research is based on the importance of legal foundations in running the country's legal system, which includes regulations governing the lives of the people. The research method used is a descriptive-analytical design with a qualitative approach, involving in-depth interviews, documentation, and participatory observation. The findings of this study indicate that one of the main challenges in implementing functional position policies is the lack of training and competency development for Civil Servants (PNS). The implication of these findings is the need to enhance the professionalism of PNS through functional position reform to strengthen the application of good governance principles in public administration. This study contributes to understanding the relationship between legal construction, functional position reform, and the effectiveness of public administration in Indonesia.